PROSES BERPIKIR SISWA BERKEMAMPUAN METAKOGNISI RENDAH DALAM MENGERJAKAN SOAL ARITMETIKA - Pratiwi, Putri Indah; Dafik, Dafik; Setiawani, Susi (Kadikma, 2017)
Abstract. This research is a descriptive qualitative research. The purpose of this research was to describe the thinking processes of students capable of Metacognition is low in an arithmetic problem. Method of data collection consists of questionnaire, tests and interviews. The subject of this research as much as 2 students are selected based on the results of questionnaire the ability of Metacognition with the lowest score. The results of this research, students capable of Metacognition indicators able fulfilled implementation of the concept but it has a disadvantage in concluded, provide examples, and suggested the idea. Keywords: The Process of Thinking, Students Capable of Metacognition Is Low, Arithmetic.